(x+7) and (x-3)
x2+5x-14 = (x+7)(x-2) when factored
It is (x+9(x-2) when factored
Both - a polynomial expression, if you like.
The actual equation itself is the polynomial. There is no polynomial for it, and your question doesn't really make sense.
x^2 + 7x -18 = (x - 2)(x + 9)
X2 - 6X + 27 = 0 what are the factors of 27 that add to - 6? None! This polynomial is unreal and does not intersect the X axis.
Factor the polynomial x2 - 10x + 25. Enter each factor as a polynomial in descending order.
x2 + 12x + 32 = (x + 8)(x + 4)